Effect of compression molding temperature on the characterization of asbestos-free composite friction materials for railway applications - Rahmad Doni, Widodo; Rusiyanto, .; Wahyudi, .; Melisa Kartika Sari, .; Deni Fajar Fitriyana, .; Siregar, Januar Parlaungan; Cionita, Tezara; Da Silva Guterres, Natalino Fonseca; Da Silva, Mateus De Sousa; Jamiluddin, Jaafar (AIMS Press, 2023)
Brake pads significantly affect the braking performance of railways under both normal and emergency operating conditions. In previous studies, brake pads were made using the hand lay-up method and produced the best properties on specimens with epoxy, rice husk, Al2O3 and Fe2O3 compositions of 50%, 20%, 15% and 15%. However, the resulting density does not meet the density standard set by PT Industri Kereta Api Indonesia (PT INKA), which is 1.7–2.4 g/cm3. To date, there has been limited research into the utilization of the compression hot molding method for the production of asbestos-free composite friction materials composed of epoxy, rice husk, Al2O3 and Fe2O3 for railway applications. In this study, we aimed to determine the effect of compression molding temperature on the characterization of composite brake pads for railway applications. The brake pad specimens were made of epoxy resin, rice husk, Al2O3 and Fe2O3 with a composition of 50%, 20%, 15% and 15%, respectively. The manufacture of composites in this study used the compression molding method with a pressure of 20 MPa for 15 min holding time. The mold temperature used were 80, 100, 120 ℃. Density, hardness, tensile, wear, thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC) tests were performed to evaluate the properties of the specimens obtained. The results demonstrated that an increase in molding temperature improved the characterization of the brake pads, with the best results achieved at a molding temperature of 120 ℃ (SP-3 specimen). SP-3 specimens had the best density, hardness, tensile properties and thermal properties compared to other specimens.